High-precision piezo-ejection ocular microdosing: Phase II study on local and systemic effects of topical phenylephrine. (January 2018) - Ianchulev, Tsontcho; Weinreb, Robert; Tsai, James C; Lin, Shan; Pasquale, Louis R
Aim: Conventional eyedropper-delivered volumes (25–50 µl) exceed the eye's usual tear-film volume (7 µl) and precorneal reservoir capacity, risking overflow and ocular/systemic complications. Piezoelectric high-precision microdosing may circumvent these limitations.Results & methodology: In this masked, nonrandomized, cross-over study, subjects (n = 12) underwent pupil dilation with topical phenylephrine (PE) administered by 32-µl eyedropper (2.5% or 10% formulation) and 8-µl electronic microdosing (10% formulation). Microdosing with PE-10% achieved comparable peak dilation as 10% eyedropper-delivery and superior dilation to 2.5% eyedropper-delivery (p = 0.009) at 75 min. Microdosing significantly reduced 20-min plasma PE levels versus PE10% eyedropper; neither treatment altered heart rate/blood pressure. Eye irritation occurred significantly less frequently with microdosing than PE10% eyedrops.Conclusion: Piezo-ejection PE microdosing achieves comparable biological effect as eyedropper dosing; reduced systemic absorption may decrease risk of systemic side effects.